Tatwir Wahdah Taklim Al-Lughah Al-Arabiyyah Elekturuniyyah Li Tholabah As-Shaf As-Tsamin Fi Al-Mahad Al-Kautsar Muhammadiyyah Sarilamak - Beni Hasti; Harmonedi Harmonedi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
One of the efforts that teachers can do to attract students to learn, one of which is by designing interesting learning media. Based on observations and interviews conducted in the eighth grade at Islamic boarding school Al-Kautsar, it was found that there was still a lack of interest in student learning so that during the learning took place students did not pay attention to the teacher, the teaching materials used were only glued to existing books, and the teacher's lack of creativity in designing learning media that was able to attract students to learn. Based on this, researchers designed a learning media in the form of an electronic module in learning Arabic. The purpose of this study is to produce Arabic learning media in the form of valid, practical and effective electronic modules so that it can help students in understanding Arabic material in the learning process. The approach used in this study is a qualitative approach to research and development methods in the ADDIE model, which consists of analysis, design, development, implementation and evaluation. The results showed that: 1) the results of the validity of learning media using electronic modules in Arabic language learning obtained were 86.8% with very valid categories, 2) the results of the practicality of learning media using electronic modules in Arabic language learning obtained from the results of the student response questionnaire, namely 94% while the results of the teacher response questionnaire were 97.5% with a very practical category, and the increase in pretest and posttest scores was analyzed using the N-gain test, which was 0.73 with a high category. With this, it can be concluded that the learning media using electronic modules in Arabic language learning are designed to be valid, practical, and effective.